Clinical Investigation:Utility of Pregestational Body Mass Index and Initial Fasting Plasma Glucose in Predicting Gestational Diabetes Mellitus. (April 2016) - Li, Ping; Yin, Yuzhu; Lin, Shuo; Cui, Jinhui; Zhou, Shuisheng; Li, Ling; Fan, Jianhui
ABSTRACT : Objective: : The present study aimed to evaluate the pregestational body mass index (preBMI) and initial fasting plasma glucose (FPG) in predicting gestational diabetes mellitus (GDM) in southern Chinese women. Study Design: : A total of 327 pregnant women were recruited from the third affiliated hospital of Sun Yat‐Sen University, Guangzhou, China. The preBMI and initial FPG at 16‐18 weeks' gestation were measured. Oral glucose tolerance test was performed at 24‐28 weeks' gestation. The sensitivity and specificity of preBMI and initial FPG as predictors for GDM were evaluated by receiver‐operator characteristic curve analysis. Results: : Both preBMI and initial FPG correlated with the 0‐hour, 1‐hour and 2‐hour plasma glucose during oral glucose tolerance test ( P < 0.05). The area under receiver‐operator characteristic curve was 0.63 (95% CI: 0.57–0.68) for preBMI and 0.68 (95% CI: 0.61–0.72) for initial FPG in diagnosing GDM. The optimal cutoff for preBMI was 21.5 kg/m 2 (sensitivity 52.1% and specificity 69.2%) and 4.6 mmol/L (sensitivity 64.6% and specificity 65.2%) for initial FPG. Interestingly, the initial FPG had a better sensitivity compared to preBMI when the specificity was the same. Multivariate logistic regression analysis showed that initial FPG but not preBMI was the independent risk factor for the later development of GDM. After adjustment for the preBMI and the maternal age, the odds ratios of initial FPG and parity were 3.57 (95% CI: 1.72–7.45) and 2.11 (95% CI: 1.20–3.72). Conclusions: : Although both preBMI and initial FPG could be used as indicators for GDM, the initial FPG may be more suitable for predicting GDM in southern Chinese women.